Hasrat Muda Sdn Bhd / Hishamudin Hasbullah ... [et al.] - Hasbullah, Hishamudin; Mohd Rosli, Mohd Asymawi; Abdul Rahim, Fatin Nadia; Idris, Azlina; Ruzman Azlee, Ruzaidee Jan; Md Nor, Mohd Nor Firdaus (2004)
As the entrepreneurs, we would like to introduce our business plan and its basic features. The idea of starting the business came to our minds because we observed that there are some imperfections in current products, which is battery manufacturing. In addition to that, for the time being this industry is considered quite new. Hence we have minimal competition over market share. We see that as an opportunity to take a piece of the industry. Because the blooming of transportation industry by the government owned companies like Proton, Perodua and Modenas, as well as government agencies such as police department, and other government agencies, we plan to tie up a tender with the government itself to assure loyal clients. The six of us decided to pull in every inch of resource we can muster to start a manufacturing company. We register the company as a private limited company under the name Hasrat Muda Sdn Bhd. consisting of the following members:-